Disarticulation of strategic planning and budget programming and its effect on CEPLAN management - Galloso Porras, Elmer Marcos (2021)
The public administration in Peru is developed through the dynamic interrelation of the different administrative systems, which are constituted by principles, norms, procedures, techniques and instruments that allow them to develop their permanent activities based on people and society. All administrative systems, in one way or another, are linked; Among them, the link between the Strategic Planning and Public Budget Systems stands out, since the first establishes the type of society to be achieved and the second is the financial expression that allows the allocation of public resources based on the results to obtain. This article has analyzed how these systems were linked in the National Center for Strategic Planning (CEPLAN) in the 2009-2018 period and how it has influenced the achievement of the entity's objectives. The main conclusion that has been obtained is that the disarticulation between the strategic planning systems and the programming of expenses has had a negative effect on the management of CEPLAN.